A contextual typology for the study of the relationship between political instability and tourism - Theocharous, Antonis L. (My University, 2010)
This paper endeavours to shed some new light onto the political dimensions of tourism, by contributing and enhancing understanding of the institutional dimensions of political instability and tourism. It aims to show, specifically, that tourism often is the result of politics, that it is inextricably intertwined sometimes with national politics, and often with international politics, social and environmental impacts, and thus has a direct and indirect influence, which cannot be ignored. To this end, at a first step a working definition of 'political instability' will be provided so as to facilitate the process of reviewing and critically assessing the extant literature. At a subsequent step, a contextual typology for the study of the relationship between political instability and tourism is developed. This typology has as its major objectives • to assist the categorisation and analysis of the relevant literature • to enable future researchers to empirically apply an analytical approach that it will delineate the basic sources of variation of the various conceptual themes relating political instability and tourism.
Keywords: Tourism; Politics; International politics; Literature